2016
DOI: 10.1007/s00441-016-2394-x
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits embryonic stem cell self-renewal and subsequent neural differentiation by modulating the let-7a-Lin28 signaling pathway

Abstract: The commonly used inhalational anesthetic, sevoflurane, can cause toxicity to the central nervous system of the developing fetus. Lin28 has been reported to regulate let-7a, thereby modulating embryo development, neurodegeneration, and even neuron-related tumorigenesis. We demonstrate that pregnant mice receiving sevoflurane treatment during the early stage of pregnancy give birth to fewer offspring presenting a lower birth weight. We have also treated mouse embryonic stem cells (mESCs) with sevoflurane for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Although some study results have shown certain anesthesia drugs may affect NSC differentiation, the ndings are con icting and controversial during different periods of brain development. For example, in a previous study, 4.1% sevo urane for 6 h repressed neural differentiation by in uencing self-renewal of mouse embryonic stem cells (mESCs) (Yi, Cai, Zhang, Wang, & Li, 2016). In another study, 7-day-old rats exposed to ketamine showed signi cantly reduced number of nestin/BrdU double-stained positive cells and GFAP/BrdU double-stained positive cells and increased number of β-tubulin III/BrdU double-stained positive cells (Huang et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although some study results have shown certain anesthesia drugs may affect NSC differentiation, the ndings are con icting and controversial during different periods of brain development. For example, in a previous study, 4.1% sevo urane for 6 h repressed neural differentiation by in uencing self-renewal of mouse embryonic stem cells (mESCs) (Yi, Cai, Zhang, Wang, & Li, 2016). In another study, 7-day-old rats exposed to ketamine showed signi cantly reduced number of nestin/BrdU double-stained positive cells and GFAP/BrdU double-stained positive cells and increased number of β-tubulin III/BrdU double-stained positive cells (Huang et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, 3% sevo urane (1.5 minimum alveolar concentration, MAC) was chosen on pregnant rats, a commonly used concentration in clinical non-obstetric surgeries. 4.1% sevo urane was commonly used in NSCs to explore the neurotoxicity of SEV in vitro in previous studies (Yi et al, 2016) (S. Liu et al, 2018. There are other studies (Y.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 3% sevo urane (1.5 minimum alveolar concentration, MAC) was chosen on pregnant rats, a commonly used concentration in clinical non-obstetric surgeries. 4.1% sevo urane was commonly used in NSCs to explore the neurotoxicity of SEV in vitro in previous studies (Yi et al, 2016) (S. Liu et al, 2018. There are other studies (Y. Zhang et al, 2019) (J. Zhang, Dong, Zhou, Zhang, & Xie, 2015) using 3% SEV in vivo and 4.1% SEV in vitro to investigate the mechanism of SEV.…”
Section: Discussionmentioning
confidence: 99%
“…3 In mouse embryonic retinas, miR-96 expression level is minimal and up-regulates following birth, peaking in adult retinas. 60,61 The mechanisms by which these effects are created have yet to be identified, impeding further research in anaesthesia neurotoxicity in the developing brain. 60,61 The mechanisms by which these effects are created have yet to be identified, impeding further research in anaesthesia neurotoxicity in the developing brain.…”
Section: Discussionmentioning
confidence: 99%